The oral microbiome in young women at different stages of periodontitis: Prevotella dominant in stage III periodontitis - Zhao, Yaqiong; Feng, Yunzhi; Ye, Qin; Hu, Jing; Feng, Yao; Ouyang, Zeyue; Zhao, Jie; Chen, Yun; Tan, Li; Chen, Ningxin; Dusenge, Marie Aimee; Su, Xiaolin; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Periodontitis progression is related to the dynamic dysbiosis of oral microbiome. We identified the dominant bacteria and the potential pathway in young women with stage-III periodontitis. Materials and methods Samples of subgingival plaque were collected from 26 young women with periodontitis (20 with stage-I and 6 with stage-III). Using 16S rRNA-sequencing, we determined the variation in oral bacterial communities of the two groups, and identified the dominant bacteria of each group. We used the Kyoto Encyclopedia of Genes and Genomes (KEGG) database to evaluate the signaling pathways related to the difference in oral bacterial composition. The role of the dominant bacteria of stage-III periodontitis was investigated in vivo and in vitro using an endoplasmic reticulum stress inhibitor. Results Young women with stage-I periodontitis had higher values for the Chao1 Index, Observed Species and Phylogenetic Diversity Whole Tree Index than those for women with stage-III periodontitis. β-diversity analyses revealed that samples could be divided into different groups according to the periodontitis stage. The most representative biomarkers of stage-III periodontitis in young women were bacteria of the phylum Bacteroidetes, its order, family and genera Bacteroidales, Prevotellaceae and Prevotella. The KEGG database revealed that the change in oral bacterial composition of young women with stage-III periodontitis may be related to protein processing in an endoplasmic reticulum pathway. Salubrinal (an endoplasmic reticulum stress regulator) controlled expression of Runx2, Col1a1, Ocn in mouse bone-marrow mesenchymal cells. Salubrinal administration showed that moderate endoplasmic reticulum stress inhibited alveolar bone loss in periodontitis induced by Prevotella intermedia lipopolysaccharide. Conclusion Differences between periodontitis stages were noted and bacteria of Prevotella species were abundant in young women with stage-III periodontitis. This phenomenon was related to protein processing in an endoplasmic reticulum pathway.